How do household tasks shape employment contracts? The provision of care in Portugal - Suleman, F.; Suleman, A. (Feminist Economics, 2019)
This study illustrates the complexities involved in outsourcing domestic work to the market. It draws on an original dataset of paid domestic workers in Portugal to examine how specific tasks interact with and explain contractual arrangements. A fuzzy cluster analysis categorizes paid domestic workers into caregivers and cleaners; however, a great degree of overlap implies that caring also entails cleaning tasks necessary for the care receiver’s well-being. A subsequent Tobit regression analysis shows that caregivers have more formal and stable contracts but earn lower wages and have longer working hours relative to cleaners. The study finds a segmentation of national origin and that some migrants are at a disadvantage in care work. The study also examines how employers deal with the idiosyncrasies of domestic work such as navigating trust-related issues.